2019
DOI: 10.1136/gpsych-2018-100042
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of hair risperidone concentration and serum level among patients with schizophrenia

Abstract: BackgroundRisperidone (RSP) has a rapid onset in vivo, low dosage and high plasma protein binding rate, therefore therapeutic drug monitoring (TDM) is needed to ensure safety in clinical treatment. However, compared with blood, hair is non-invasive, safe, non-infectious and easy to transport and store.AimsThis study aims to investigate the correlations among the drug concentrations of RSP in hair and serum, which provides an experimental basis to explore hair as a novel biomaterial to meet the needs of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(28 reference statements)
1
7
0
Order By: Relevance
“… These results agreed with our findings regarding the correlations for clozapine and norclozapine. Our results are in line with those reported by Sun et al, who reported that dosage showed no significant correlation with the hair concentration of risperidone (r = 0.207, P = 0.241, n = 34) or 9‐OH‐risperidone (r = −0.194, P = 0.271, n = 34).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“… These results agreed with our findings regarding the correlations for clozapine and norclozapine. Our results are in line with those reported by Sun et al, who reported that dosage showed no significant correlation with the hair concentration of risperidone (r = 0.207, P = 0.241, n = 34) or 9‐OH‐risperidone (r = −0.194, P = 0.271, n = 34).…”
Section: Resultssupporting
confidence: 93%
“…Information on administered doses and related hair concentrations has scarcely been reported for most antidepressants and antipsychotics. Some studies showed a good correlation between drug concentration in the proximal hair section of chronic users and administered dose, while other studies reported no correlation or a poor correlation . Moreover, many variables (hair melanin content, age, enzymatic activity, cosmetic hair treatment, and hair care habits) can cause large interindividual differences.…”
Section: Introductionmentioning
confidence: 99%
“…The female gender, younger age, and increased stress reactions were associated with the increased risk for depression. 37 As such, psychological inventions are required for both the medical workers and nonmedical staff. 38 This study has several limitations that should be taken into account.…”
mentioning
confidence: 99%
“…A greater part of the controlled dose studies was done in the 1990s and early 2000s after which research on controlled dose studies seemed to decrease. The more recent work of Sun et al, 58 Licata et al, 23 and Wang et al 37 is, therefore, a favorable development toward a better understanding and statistical base of concentrations of antidepressants and antipsychotics in human hair. Collaboration with medical stations where patients are treated with antidepressants and antipsychotics serves as a good base for retrospective dose studies with a proper ethical foundation.…”
Section: Resultsmentioning
confidence: 99%